Еко-винаходи: новинки, покликані врятувати навколишнє середовище України - Гуренко, Ірина Вікторівна; Дейнега, М. С. (ГО "СФБЖДЛ", 2016)
Розглянуто деякі варіанти найцікавіших винаходів українців за період незалежності, які істотно можуть вирішити проблеми поліпшення екологічного стану території України.

Some options of the most interesting inventions of Ukrainians during independence who can significantly solve problems of improvement of an ecological condition of the territory of Ukraine are considered.
Eco-invention: new products, designed to save the environment of Ukraine
Keywords: екологічний стан; поліпшення; пластик; велосипед бамбуковий; води стічні; очистка біологічна; what inventions; ecological condition of Ukraine; improvement